Molecular genetic biotechnologies – the way to the welfare of the people and increasing of agriculture profitability - Potopalsky, A.I.; Bolsunova, O.I.; Zaika, L.A. (Вiopolymers and Cell, 2013)
We have designed and offered a comprehensive approach to solving several problems in modern agriculture and human health. It is based on the original use of biotechnology. The mechanisms of alkylation of amines, nucleic acids and their derivatives by etylenimin components have been investigated. Alkylation products were purified and characterized, their biological activity, studied in various systems, was identified as well as their antitumor, antiviral and immunomodulatory effects. Based on the development of original methods of natural substances modification and the use of obtained products for the regulation of molecular biological processes a new scientific direction has been created. This article presents the results of over 50-years-old research on development of original biotechnological methods. Нами створено і запропоновано комплексний підхід до вирішення багатьох проблем сучасності в галузі сільського господарства і здоров’я людини. Він базується на застосуванні оригінальних біотехнологій. Досліджуються механізми алкілування амінів, нуклеїнових кислот та їхніх компонентів похідними етиленімінів. Продукти алкілування очищено і охарактеризовано, виявлено їхню біологічну активність, досліджувану в різних системах, а також їхні протипухлинні, противірусні та імуномодулюючі ефекти. На основі розробки оригінальних методів модифікації природних речовин та використання одержаних продуктів для регуляції молекулярно-біологічних процесів створено новий науковий напрямок. Викладено результати понад 50-річних науково-практичних доcліджень зазначених сполук Нами создан и предложен комплексный подход к решению многих проблем современности в области сельского хозяйства и здоровья человека. Он основан на применении оригинальных биотехнологий. Исследуются механизмы алкилирования аминов, нуклеиновых кислот и их компонентов производными этилениминов. Продукты алкилирования очищены и охарактеризованы, выявлена их биологическая активность, исследуемая в различных системах, а также их противоопухолевые, противовирусные и иммуномодулирующие эффекты. На основе разработки оригинальных методов модификации природных веществ и применения полученных продуктов для регуляции молекулярно-биологических процессов создано новое научное направление. Изложены результаты более чем 50-летних научно-практических исследования указанных соединений